HUBUNGAN PERSEPSI REMAJA TENTANG KEPEDULIAN ORANGTUA DAN KETERSEDIAAN MEDIA INFORMASI KESEHATAN MASYARAKAT DENGAN PERILAKU PACARAN BERISIKO DI SMK X SEMARANG TAHUN 2017 - Paska Aprina Br Purba; Sri Winarni; Dharminto Dharminto; Farid Agusyahbana (Jurnal Kesehatan Masyarakat (Undip), 2017)
PILAR PKBI survey conducted in 2015 in City and District Semarang obtained that the behavior of teen courtship has been heading towards a very risky. Even adolescents who are still in school have sexual intercourse. In the location where the study was obtained 2 cases of students were issued due to pregnancy cases outside marriage in 2016. The purpose of this study is to analyze the relationship between adolescent perceptions about parental care and the availability of reproductive health information media with risky dating behavior in students of SMK X Semarang in 2017.Type of research explanatory research with cross sectional method. The population of this study are all students of class X and XII SMK X Semarang who ever dating and are courting 169 people. The sample in this study is the total population, which is 146 people.The result of univariate analysis shows that the highest percentage of teenagers is female teenager (79,5%) where age at most is age 17 year (41,8%). The result of spearman Rank correlation statistic test shows that there is no significant correlation between adolescent perception about parental care (p = 0,376) and availability of media of reproduction health information (p = 0,310) with risk dating behavior at student of SMK X Semarang 2017. Suggestion for parents to become teenage friends in sharing their problems, paying attention through text messages / direct calls while outdoors, providing knowledge to adolescents on issues related to reproductive health.